Randomized controlled trial of perioperative antimicrobial therapy based on the results of preoperative bile cultures in patients undergoing biliary reconstruction. (6th May 2017) - Okamura, Kunishige; Tanaka, Kimitaka; Miura, Takumi; Nakanishi, Yoshitsugu; Noji, Takehiro; Nakamura, Toru; Tsuchikawa, Takahiro; Okamura, Keisuke; Shichinohe, Toshiaki; Hirano, Satoshi
Abstract: Background: The high frequency of surgical site infections (SSIs) after hepato‐pancreato‐biliary (HPB) surgery is a problem that needs to be addressed. This prospective, randomized, controlled study examined whether perioperative prophylactic use of antibiotics based on preoperative bile culture results in HPB surgery could decrease SSI. Methods: Participants comprised 126 patients who underwent HPB (bile duct, gallbladder, ampullary, or pancreatic) cancer surgery with biliary reconstruction at Hokkaido University Hospital between August 2008 and March 2013 (UMIN Clinical Trial Registry #00001278). Before surgery, subjects were randomly allocated to a targeted group administered antibiotics based on bile culture results or a standard group administered cefmetazole. The primary endpoint was SSI rates within 30 days after surgery. Secondary endpoint was SSI rates for each operative procedure. Results: Of the 126 patients, 124 were randomly allocated (targeted group, n = 62; standard group, n = 62). Frequency of SSI after surgery was significantly lower in the targeted group (27 patients, 43.5%) than in the standard group (44 patients, 71.0%; P = 0.002). Among patients who underwent pancreaticoduodenectomy and hepatectomy, SSI occurred significantly less frequently in the targeted group ( P = 0.001 and P = 0.025, respectively). Conclusions: This study demonstrated that preoperative bile culture‐targeted administration of prophylactic antibiotics decreased SSIs following HBP surgery with biliary reconstruction. Highlight: In this randomized controlled trial of perioperative antimicrobial prophylaxis in hepato‐pancreato‐biliary surgery with biliary reconstruction, Okamura and colleagues compared the efficacy of bile culture‐targeted versus standard administration of prophylactic antibiotics. They found that administration of antibiotics selected based on preoperative bile culture results reduced the number of surgical site infections.